2005
DOI: 10.1124/jpet.104.080101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Serotonergic Activity and Reinforcing Effects of a Series of Amphetamine Analogs

Abstract: It has been reported that among drugs with mixed actions on central nervous system monoamine systems, increased serotonergic activity is associated with decreased potency as a reinforcer. The present experiment was designed to examine this relationship for amphetamine analogs that varied in serotonin releasing potency and to evaluate whether serotonergic actions can affect reinforcing efficacy. Compounds PAL 313 and 314 are para-and meta-methylamphetamine, respectively. PAL 303 and 353 are para-and meta-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
209
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(230 citation statements)
references
References 32 publications
18
209
2
1
Order By: Relevance
“…Among amphetamine-like drugs that are not as selective for 5-HT releasing activity, Ritz and Kuhar (1989) reported a negative correlation between potency as a reinforcer and binding affinity at the 5-HT transporter (SERT). We have recently reported self-administration results with a series of amphetamine analogs in monkeys that reached similar conclusions (Wee et al 2005).…”
Section: Introductionsupporting
confidence: 54%
“…Among amphetamine-like drugs that are not as selective for 5-HT releasing activity, Ritz and Kuhar (1989) reported a negative correlation between potency as a reinforcer and binding affinity at the 5-HT transporter (SERT). We have recently reported self-administration results with a series of amphetamine analogs in monkeys that reached similar conclusions (Wee et al 2005).…”
Section: Introductionsupporting
confidence: 54%
“…Serotonergic activity of stimulants has been proposed to influence relative reinforcing efficacy of compounds with mixed monoamine actions (Roberts et al, 1999;Wee et al, 2005). It, however, seems unlikely that differences in the serotonergic activity of the drugs in the present study contributed to the differences in relative reinforcing efficacy observed under the PR schedule.…”
Section: Discussionmentioning
confidence: 64%
“…This compound is equipotent as a releaser of dopamine, norepinephrine and 5-HT [4], It also shows low affinity for 5-HT 2 receptors [15]. However, with respect to 5-HT release, 4-MA was significantly more potent compared to amphetamine [4].…”
Section: Discussionmentioning
confidence: 99%
“…Green et al studied the effect of MDMA on body temperature and found that its administration to rats produces hyperthermia if animals are housed in normal or warm ambient room temperature conditions ( 20°C), but hypothermia when in cool conditions ( 17°C) [19]. Perhaps the difference between both drugs is that the potency and selectivity of 4-MA as serotonin releaser is higher than other amphetamine derivatives [4]. A slight tachyphylaxis to this effect was found because after a repeated administration schedule, the maximum of hypothermia after the fourth administration significantly differed from the first one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation